Correlation between large amplitude oscillatory shear (LAOS) and steady shear of soft solids at the onset of the fluid rheological behavior. (8th November 2016) - Coblas, Daniela; Broboana, Diana; Balan, Corneliu
Abstract: The paper is concerned with the experimental investigations of soft solids rheology at the onset of the fluid behavior. The aim of the work is to find the correlation between the dynamics moduli measured in MAOS and LAOS oscillatory regime and the data obtained in simple shear experiments. The tested samples are represented by colloidal systems and suspensions (impression material and a cosmetic cream), both being characterized by a yield state. The present study explores the idea that yield state, determined in simple shear as the onset of the plateau in flow curve, corresponds to the MAOS region and the yield point coincides with the location where the viscous modulus discloses a relatively peak against the strain amplitude. It is proved experimentally that flow onset, up to now manly determined in simple shear, is also detectable using the oscillatory strain amplitude sweep test and corroborated by the FT-rheology analysis of the data. So, the yield point is more precisely characterized by a critical value of strain, rather than a unique value of the yield stress. Since the yield state is one of the main rheological characteristic of soft solids/matter rheology, it is of major interest to have at hand a procedure for characterization the onset of material fluid behavior and to detect possible presence of wall depletion phenomena. The results of this study demonstrate that for materials in which the yield state is present qualitative and quantitative relations between the data from simple shear and oscillatory tests can be established. Graphical abstract: Highlights: The yield point is characterized by a critical value of the strain deformation γ c r . γ c r corresponds to the maximum of G ″ in the MAOS. γ c r defines also the plateau disclosed by the flow curve. FT-rheology analysis emphasis the existence of yield state and the onset of the flow.